Material and compressional properties of Irvingia gabonensis (O’Rorke) Bail polymers (2022)
The physicochemical, material and compressional properties of the Irvingia gabonensis (O’Rorke) Bail polymer were evaluated and compared with xanthan gum and hydroxypropylmethylcellulose (HPMC). The Irvingia polymer was extracted using established methods and processed using two methods of drying, that is, oven-drying and freeze-drying. The compression mechanisms were evaluated using the Heckel and Kawakita equations. The mechanical strength of the tablets was evaluated using crushing strength and friability. The results showed that the Irvingia kernel polymer was slightly acidic, free of heavy metals, with irregularly shaped particles that exhibited some degree of crystallinity. The Irvingia kernel polymer was directly compressible and formed intact non-disintegrating tablets similar to the standard polymers. The Heckel and Kawakita equations indicated that the Irvingia polymer deformed plastically with fast onset and a high amount of plastic deformation compared to xanthan gum and HPMC. The freeze-dried Irvingia gum showed significantly (p<0.05) higher crushing strength and lower friability than the oven-dried polymer. The results indicated that the drying method had a significant impact on the compression characteristics as well as the properties of the polymer tablets. Thus, the Irvingia polymer could be more suitable for the formulation of tablets using direct compression.